Structural and dynamic analysis of G558R mutation in chicken TSHR gene shows altered signal transduction and corroborates its role as a domestication gene. (20th November 2019) - Grottesi, A.; Gabbianelli, F.; Valentini, A.; Chillemi, G.
Summary: The thyroid‐stimulating hormone receptor ( TSHR ) has been indicated as a putative domestication gene in chicken. Comparison of WGS identified a variant in residue 558 of the transmembrane domain (TM) of TSHR, where the domestic chicken (GGD) presents an arginine, whereas the red jungle fowl (RJF) shares a conserved glycine with other vertebrates. This variant has been demonstrated to be associated with phenotypes that are important for domestication and related to thyroid regulation, such as less fearful behavior, reduced aggressive behavior and reduced dependence on seasonal reproduction in GGD as compared with RJF. By means of molecular dynamics simulations, we highlighted the structural and dynamic differences of variant Gly558Arg in the TSHR TM domain. Alterations in TM helix flexibility, structure and protein overall motion are described. The so‐called 'arginine snorkeling' of residue 568 in GGD is observed and we hypothesize it as the originating force that produces the observed whole‐protein perturbation in the helix bundle dynamics, capable of altering the TSHR signal transduction. The results are discussed in the context of their implications for a better understanding of biological mechanisms in chicken under control of the thyroid, such as body metabolism, as well as for their usefulness in biomedical research.